Duration Of Ventilation Support Usage And Development Of Ventilator-Associated Pneumonia: When Is The Most Time At Risk? - Ricky Indra Alfaray; Muhammad Iqbal Mahfud; Rafiqy Sa'adiy Faizun (Indonesian Journal of Anesthesiology and Reanimation, 2019)
Introduction: Ventilator-Associated pneumonia (VAP) is pneumonia that occurs in patients who have been mechanically ventilated for a duration of more than 48 hours. The duration of ventilator use was identified as a risk factor which is a trigger of VAP. Objective: This study aimed to determine the association between the duration of ventilator use and the incidence of VAP in patients in the Intensive Care Unit of Dr. Mohammad Hoesin General Hospital, Palembang. Method and Material: This study was an observational analytic study using a cross-sectional design. The samples were all patients who use a ventilator for more than 48 hours at the ICU room period of July 1, 2014, to June 30, 2015. Data were obtained from the patient's medical records of a total of 146 patients, but the number of patients who comply with the criteria was 106 patients. Result and Discussion: Out of the 106 samples, 41 patients (38.7%) developed VAP and 65 patients (61.3%) did not develop VAP. The analysis using Chi-Square test showed that patients who used ventilator for >5 days had an OR = 3.273 compared to patients using ventilator 2-5 days (p-value = 0.016; 95% CI = 1.223 to 8.754). Conclusion: There is a significant association between the duration of ventilator use and the incidence of VAP in patients at the ICU of Dr. Mohammad Hoesin General Hospital, Palembang. Patients using ventilators for more than 5 days 3,386 times more at risk of developing VAP compared to patients using ventilators 2-5 days. The riskiest time for the patient using ventilator was more than 5 days of usage. And, the mortality rate of VAP patients was 63.4% from 41 patients while the mortality rate of whole ICU patients was 50.9%.